A new genus with a new species of Cantacaderinae (Heteroptera: Tingidae) from Argentina - Carpintero, Diego L.; Montemayor, Sara I. (Zootaxa, 2005)
A new genus Pampacader with a new species P. cicchinoi is described in the tribe Phatnomatini Drake & Davis of Cantacaderinae Stål. This genus is the first member of this subfamily and tribe recorded from so austral an area (Buenos Aires province, Argentina). Only two genera of Phatnomatini were known belonging to a northern province (Misiones) of Argentina.